Internet connectivity disruption in Saudi Arabia (Saudi Arabia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Saudi Arabia. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: SA-2026-0054. Severity: critical. Confidence: 70%